Maternal and neonatal outcome following induction with misoprostol versus oxytocin in primigravidae at term - Maharjan, Rony; Thapa, Ganesh (Journal of General Practice and Emergency Medicine of Nepal, 2018)
Introduction: The purpose of this study was to compare the outcome of vaginally administered misoprostol versus intravenously infused oxytocin for labor induction in term primigravidas. Method:A total of 106 term primigravidas with indication for induction were assessed for eligibility to enter the study. Those meeting the inclusion criteria were assigned to two groups, women induced in TUTH as misoprostol group and WRH as oxytocin group. The misoprostol group received 50 mcg every 6 hours upto 2 doses.The oxytocin group received an infusion of 5 units which was gradually increased upto 60 drops/min maximum of 3 pints. The outcome of labour was compared in the two groups. Result: Fifty-three women received oxytocin, and 53 women received misoprostol. Maternal demographics, pre induction Bishop scores, were similar between both the groups. Mean induction to delivery interval were similar in both groups (10.04 vs 10.64 , P value = 0.68). Caesarean delivery rate was higher in oxytocin (34%) compared with misoprostol (13%). There was no difference in maternal complications or neonatal outcome between the two groups. Conclusion: Misoprostol is a safe and effective drug for the induction of labour in term primigravidas. Failure is seen less with misoprostol and caesarean sections are less frequently indicated as compared to oxytocin.